История отечественного государства и права: Учебное пособие / Валерий Кулиевич Цечоев, Валерий Кулиевич - Цечоев Валерий Кулиевич (Серия "Юридическое образование", 2003)
Экземпляры: (20160227) / Инвентарный номер: 39983 / Цена: / Авт.знак: Ц55 / ББК: 67.400я73